Myoinositol and methyl stearate increases rifampicin susceptibility among drug‐resistant Mycobacterium tuberculosis expressing Rv1819c. (5th January 2023) - Nirmal, Christy Rosaline; Rajadas, Sam Ebenezer; Balasubramanian, Mahizhaveni; Mohanvel, Sucharitha Kannappan; Aathi, Muthu Sankar; Munishankar, Saravanan; Chilamakuru, Naresh Babu; Thiruvenkadam, Kannan; Pandiya Raj, Ajith Kumar; Paraman, Ramalingam; Dusthackeer, Azger
Abstract: The alarming increase in multidrug resistance, which includes Bedaquiline and Delamanid, stumbles success in Tuberculosis treatment outcome. Mycobacterium tuberculosis gains resistance to rifampicin, which is one of the less toxic and potent anti‐TB drugs, through genetic mutations predominantly besides efflux pump mediated drug resistance. In recent decades, scientific interventions are being carried out to overcome this hurdle using novel approaches to save this drug by combining it with other drugs/molecules or by use of high dose rifampicin. This study reports five small molecules namely Ellagic acid, Methyl Stearate, Myoinositol, Rutin, and Shikimic acid that exhibit synergistic inhibitory activity with rifampicin against resistant TB isolates. In‐silico examinations revealed possible blocking of Rv1819c—an ABC transporter efflux pump that was known to confer resistance in M. tuberculosis to rifampicin. The synergistic anti‐TB activity was assessed using a drug combination checkerboard assay. Efflux pump inhibition activity of ellagic acid, myoinositol, and methyl stearate was observed through ethidium bromide accumulation assay in the drug‐resistant M. tuberculosis clinical strains and recombinant Mycobacterium smegmatis expressing Rv1819c in coherence with the significant reduction in the minimum inhibitory concentration of rifampicin. Cytotoxicity of the active efflux inhibitors was tested using in silico and ex vivo methods. Myoinositol and methyl stearate were completely non‐toxic to the hematological and epithelial cells of different organs under ex vivo conditions. Based on these findings, these molecules can be considered for adjunct TB therapy; however, their impact on other drugs of anti‐TB regimen needs to be tested. Abstract : Active small molecules from dukes' database were retrieved and docked against Multidrug Efflux Pump Rv1819c protein. The small molecule inhibitors were shortlisted and validated in silico based on the glide score. The minimal inhibitory concentrations (MIC) of the lead molecules were validated against MDR‐TB and XDR‐TB clinical isolates individually and in combination with Rifampicin. Furthermore, MIC was identified individually and in combination with rifampicin and isoniazid against recombinant Rv1819c. We report that methyl stearate and Myo inositol could be a potent molecule to reduce the MIC of RMP in the drug‐resistant clinical isolates and revert it back to be a rifampicin‐sensitive strain.